Topographic Maps within Brodmann's Area 5 of Macaque Monkeys - Seelke, Adele M. H. (Oxford University Press, 2012)
Brodmann's area 5 has traditionally included the rostral bank of the intraparietal sulcus (IPS) as well as posterior portions of the postcentral gyrus and medial wall. However, different portions of this large architectonic zone may serve different functions related to reaching and grasping behaviors. The current study used multiunit recording techniques in anesthetized macaque monkeys to survey a large extent of the rostral bank of the IPS so that hundreds of recording sites could be used to determine the functional subdivisions and topographic organization of cortical areas in this region. We identified a lateral area on the rostral IPS that we term area 5L. Area 5L contains neurons with receptive fields on mostly the shoulder, forelimb, and digits, with no apparent representation of other body parts. Thus, there is a large magnification of the forelimb. Receptive fields for neurons in this region often contain multiple joints of the forelimb or multiple digits, which results in imprecise topography or fractures in map organization. Our results provide the first overall topographic map of area 5L obtained in individual macaque monkeys and suggest that this region is distinct from more medial portions of the IPS.